The Empty Space: A Book about the Theatre: Deadly, Holy, Rough, Immediate - Brook, Peter (New York Touchstone, 1996)
First published in 1968, The Empty Space is a timeless analysis of theatre, from perhaps the most influential director of the twentieth century. In The Empty Space, groundbreaking director Peter Brook draws on a life in love with the stage to explore the issues facing any theatrical performance. Here he describes important developments in theatre from the last century, as well as smaller scale events, from productions by Stanislavsky to the rise of Method Acting, from Brecht?s revolutionary alienation technique to the free form happenings of the 1960s, and from the different styles of such great Shakespearean actors as John Gielgud and Paul Scofield to a joyous impromptu performance in the burnt-out shell of the Hamburg Opera just after the war. Passionate, unconventional, and fascinating, his book shows how theatre defies rules, builds and shatters illusions, and creates lasting memories for its audiences.
Keywords: Play (theater)